Motivational Strategies for Stroke Rehabilitation: A Descriptive Cross-Sectional Study - Oyake, Kazuaki; Suzuki, Makoto; Otaka, Yohei; Tanaka, Satoshi (Frontiers in Neurology, 2020)
Background: The addition of motivational strategies to a rehabilitation program is thought to enhance patient adherence and improve outcomes. However, little is known about how rehabilitation professionals motivate stroke patients during rehabilitation. The primary objective of this study was to provide a comprehensive and quantitative list of motivational strategies for stroke rehabilitation. In addition, we aimed to examine 1) whether professionals with more clinical experience used a higher number of motivational strategies, 2) the purpose for using each strategy, and 3) the information considered when choosing strategies. Methods: This descriptive, cross-sectional study was conducted using a web survey with a convenience sample of 407 rehabilitation professionals including physicians, nurses, physical therapists, occupational therapists, and speech-language-hearing therapists. Results: We received data for 362 participants. Fifteen strategies were found to be used by more than 75% of the respondents to motivate their patients. Almost all of the respondents reported that they actively listened to and praised their patients to increase patient adherence to rehabilitation programs. Respondents with more clinical experience tended to use a higher number of motivational strategies (rho = 0.208, p < 0.001). For 11 of the 15 strategies selected by more than 75% of the respondents, the highest percentage of respondents reported that they used the strategies to make rehabilitation worthwhile for their patients. The majority of respondents reported that they decided which motivational strategy to use by considering comprehensive information regarding the patient health condition, environmental factors, and personal factors. Conclusions: The comprehensive list of motivational strategies obtained may be useful for increasing patient adherence to rehabilitation, especially for professionals with less clinical experience. Furthermore, our findings regarding the purpose for using each strategy and the information considered when choose strategies might help rehabilitation professionals to optimally utilize the motivational strategy list.